E2F7 drives autotaxin/Enpp2 transcription via chromosome looping: Repression by p53 in murine but not in human carcinomas - Lin, Kuan-Hung; Lee, Sue Chin; Dacheux, Mélanie A; Norman, Derek D; Balogh, Andrea; Bavaria, Mitul; Lee, Hsinyu; Tigyi, Gabor (The FASEB journal, 2023)
Dysregulation of the autotaxin (ATX, Enpp2)-lysophosphatidic acid (LPA) signaling in cancerous cells contributes to tumorigenesis and therapy resistance. We previously found that ATX activity was elevated in p53-KO mice compared to wild-type (WT) mice. Here, we report that ATX expression was upregulated in mouse embryonic fibroblasts from p53-KO and p53 mutant mice. ATX promoter analysis combined with yeast one-hybrid testing revealed that WT p53 directly inhibits ATX expression via E2F7. Knockdown of E2F7 reduced ATX expression and chromosome immunoprecipitation showed that E2F7 promotes Enpp2 transcription through cooperative binding to two E2F7 sites (promoter region -1393 bp and second intron 996 bp). Using chromosome conformation capture, we found that chromosome looping brings together the two E2F7 binding sites. We discovered a p53 binding site in the first intron of murine Enpp2, but not in human ENPP2. Binding of p53 disrupted the E2F7-mediated chromosomal looping and repressed Enpp2 transcription in murine cells. In contrast, we found no disruption of E2F7-mediated ENPP2 transcription via direct p53 binding in human carcinoma cells. In summary, E2F7 is a common transcription factor that upregulates ATX in human and mouse cells but is subject to steric interference by direct intronic p53 binding only in mice.